The Growth of Muslim Friendly and Halal Tourism in Inbound and Outbound Travel Market - Ahmad Puad, Mat Som; Muhamad Fazil, Ahmad; Satoshi, Masutan (2016)
As the growth of the Muslim travel market is a new phenomenon, many different terminology and definitions have been used to refer to Muslim friendly and halal tourism market segment by academics, media and other organizations. In a general term, Muslim friendly tourism is defined as ‘halal conscious travelers, traveling for any purpose, which is halal (permissible)’. The fact is the growth of the Muslim travelers, especially the middle class and younger population, has meant that Muslim travelers are becoming a significant segment, which will affect the global tourism industry. Their eagerness to explore new experiences and destinations, coupled with increased awareness of faith-based needs, is now driving the global demand for Muslim friendly tourism products and services. By reviewing secondary data and conducting interviews, this study aims to investigate factors influencing and constraints impeding the growth of MFT in inbound and outbound travel market in Far Eastern countries. Malaysia’s success story on MFT is primarily driven by the government’s commitment to identify the Muslim market as a priority market, which allows the country to top the Global Muslim Travel Index for the sixth consecutive year. In another example, the study found that the number of inbound Muslim tourists to Japan has been increasing considerably in recent years, and while the country has only a very small percentage of Muslim population, tourist associations and businesses have ramped up efforts to upgrade facilities and services to cater to Muslim’s tourist market.